KNOWLEDGE AND AWARENESS OF HAZARDS ASSOCIATED WITH THE USEOF COTTON BUDS IN SAUDI COMMUNITY - Akram Ibrahem Alwasse et al (Baqai Journal of Health Sciences)
Cotton buds are commonly used for a variety of purposes such as to clean the ears, remove wax, in case of itching in the ear, aural toilet in discharging ears and some time as a habit. The current study aims to explore the level of awareness and knowledge among the Saudi community regarding the hazards associated with using cotton buds for ears cleaning. A cross-sectional descriptive survey has been performed over a two weeks period on a sample composed of 93 individuals where a pre-designed questionnaire was filled by the participants. The results showed that there is a significant lack of knowledge and awareness among the community members regarding the hazards and further complications that could result from using cotton buds for ears cleaning. Moreover, findings of the study show that there is a weakness in providing the correct information and guidelines about the risk of using cotton buds. It is concluded that Saudi community has poor awareness and knowledge levels regarding the hazards associated with the use of cotton buds. Therefore, it is recommended that intensive awareness campaigns are needed to educate people and increase their knowledge level.